Analisis Morfometri Komparatif untuk Penilaian Risiko Banjir di Sub DAS Alo dan Molamahu, Kabupaten Gorontalo - Indrawan; Talha Dangkua; Ahmad Syamsurijal S; Risman Jaya (Jurnal Penelitian Pendidikan IPA, 2025)
This study conducts a comparative morphometric analysis of the Alo and Molamahu sub-watersheds, located in the upstream Limboto Watershed, Gorontalo Province, Indonesia, to assess flood risk. Using the National Digital Elevation Model (DEMNAS) with an 8-m spatial resolution, classical morphometric parameters were derived through remote sensing and Geographic Information System (GIS) techniques. Both sub-watersheds share a maximum stream order of 4 and exhibit relatively high drainage density and stream frequency, indicating rapid surface runoff. However, the Molamahu sub-watershed is larger, steeper, and has a higher ruggedness number than Alo, suggesting greater erosion potential and higher susceptibility to landslides and flash floods. In contrast, Alo shows gentler slopes but remains flood-prone due to short overland flow paths. The analysis demonstrates that morphometric characteristics directly influence flood dynamics, highlighting the need for tailored watershed management. Recommended strategies include erosion control and slope stabilization in Molamahu, and water retention measures in Alo, supported by broader reforestation efforts across the Limboto system.